PENGARUH PENERAPAN MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN MEDIA BAAMBOOZLE TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA DI SMP NEGERI 4 SUNGAI RAYA - Gina, Gina (UNIVERSITAS TANJUNGPURA, 2025)
Although mathematics is essential for helping students develop their critical thinking abilities, it is frequently seen as challenging, which lowers motivation and achievement, especially when it comes to the study of connections and functions. The purpose of this study os to examine how students’ motivation and learning results in mathematics are affected when the Game Based Learning (GBL) paradigm is implemented with the help of Baamboozle media. With a post-test-only control group design, the study used an experimental approach with 65 eighth-grade students split into two groups: a control group (30 students) that used cooperative learning and an experimental group (35 students) that used GBL-Baamboozle. A learning achievement exam and a motivation questionnaire were used to gather data, and t-tests and effect size calculations were used for analysis. The findings revealed a significant effect of GBL-Baamboozle on learning motivation (p = 0.000; d = 2.22) and learning outcomes (p = 0.000; d = 2.28), both categorized as high. These results indicate that the use of GBL supported by Baamboozle effectively enhances students’ engagement and academic performance in mathematics. Therefore, technology-assisted game-based learning can be considered a promising and innovative strategy to improve mathematics instruction at the secondary school level.